2014
DOI: 10.1097/iae.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

Subfoveal Choroidal Thickness Change After Intravitreal Ranibizumab for Idiopathic Choroidal Neovascularization

Abstract: In patients with unilateral ISCNV, intravitreal ranibizumab therapy was associated with a thinning of an abnormally thick subfoveal choroid, marginally in association with a parallel decrease in retinal foveal thickness. It remained elusive whether the choroidal thinning was due to a direct pharmacological effect of ranibizumab or whether it was secondary due to the foveal retinal thinning. In view of the significant differences in SFCT between affected eyes and unaffected contralateral eyes at baseline and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The result is consistent with previous studies that showed no subfoveal CT change in eyes with CVH after ranibizumab injections 4,6 and reduction of CT in eyes with idiopathic subfoveal CNV and AMD (probably without CVH). 23,24 In the present study, furthermore, the greater reduction of subfoveal PED height was achieved in aflibercept-treated eyes, which is also in line with a previous report on the reduction of PED height after switching to aflibercept from prior anti-VEGF therapy. 25 Aflibercept reduced the thickness and number of fenestrations of the choriocapillaris in monkey eyes more profoundly than ranibizumab, possibly by an interaction between an Fc fragment and other molecules.…”
Section: Discussionsupporting
confidence: 94%
“…The result is consistent with previous studies that showed no subfoveal CT change in eyes with CVH after ranibizumab injections 4,6 and reduction of CT in eyes with idiopathic subfoveal CNV and AMD (probably without CVH). 23,24 In the present study, furthermore, the greater reduction of subfoveal PED height was achieved in aflibercept-treated eyes, which is also in line with a previous report on the reduction of PED height after switching to aflibercept from prior anti-VEGF therapy. 25 Aflibercept reduced the thickness and number of fenestrations of the choriocapillaris in monkey eyes more profoundly than ranibizumab, possibly by an interaction between an Fc fragment and other molecules.…”
Section: Discussionsupporting
confidence: 94%
“…Clinical studies on adults showed that lower best corrected visual acuity was associated with a thinner choroid (also called leptochoroid), in particular with a subfoveal choroid thinner than 30 μm [12], and that some macular diseases are associated with an abnormal SFCT. To cite examples, patients with central serous chorioretinopathy had a thickened SFCT in the affected eye as well as in the contralateral unaffected eye [13,14], patients with polypoidal vascular choroidopathy showed an increased SFCT in association with a dilatation of the large choroidal vessels [1518], patients idiopathic subfoveal choroidal neovascularization showed an abnormally thick SFCT which decreases after intravitreal ranibizumab injection [19,20], patients after a non-arteritic anterior ischemic optic neuropathy had an abnormally thin SFCT [21], and patients with age-related macular degeneration, long-standing retinal vein occlusions, open-angle glaucoma or with diabetes and diabetic retinopathy exhibited a normal thickness of the subfoveal choroid [2225]. In pilot studies, SFCT was additionally correlated with estimated cerebrospinal fluid pressure and cognitive function in adults [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…14 Choroidal changes following anti-VEGF therapy have been reported in other types of CNV, such as polypoidal choroidal vasculopathy (PCV) 15 and idiopathic CNV. 19,20 Patients with these types of CNV show significant decreases in subfoveal choroidal thickness (SFCT) following the therapy. 15,19,20 In myopic CNV, few studies have described choroidal thickness changes after anti-VEGF therapy.…”
mentioning
confidence: 99%